Peningkatan Hasil Belajar Materi Kelipatan Persekutuan Terkecil Melalui Permainan Tradisional Congklak Pada Siswa Kelas IV Sekolah Dasar Negeri 13 Merawang - Yuni Artika; Vika Martahayu; M.Iqbal Arrosyad (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
The aim of the study is improving students learning outcomes through the use of congklak media in mathematics lessons on the topic of Least Common Multiple (LCM). The study employs a descriptive qualitative method with a sample of 21 fourth-grade students from State Elementary School 13 Merawang. The Classroom Action Research was conducted over two cycles, each consisting of two meetings. The stages of classroom action research include planning, implementation, observation, and reflection. Based on the learning process results using congklak media, there was a significant improvement in student learning outcomes, as evidenced by the number of students meeting the minimum mastery criteria and the average class score. In the first cycle, the number of students meeting the mastery criteria was 33.33 percent in the first meeting and 47.61 percent in the second meeting. In the second cycle, the number of students meeting the mastery criteria increased to 76.20 percent in the first meeting and 95 percent in the second meeting. The average class score showed a gradual improvement, reaching 80.47 in the second cycle. The implementation of learning using congklak media was able to significantly enhance students' learning outcomes, achieving a significant number of students meeting the mastery criteria in one class.